The perceived impact of working agreements toward employed female in the accounting profession: evidence from Iran. Issue 2 (15th January 2021) - Zarei, Hamid; Yazdifar, Hassan; Soofi, Farideh
Abstract : Purpose: After graduation, many female accountants tend to ordinarily have professional work experience to obtain an ideal position in the career; but under the influence of both internal (in the profession) and external (in life) adverse conditions, the application of their potential talent would be failed and they cannot utilize their abilities to progress in the career. Relevant studies in this field are in developed countries with minimal attention to females in other countries. This study contributes to the literature by examining the case in a developing country–Iran. Design/methodology/approach: A mixed-method study was undertaken to gather data by a postal questionnaire distributed in 2016–2017 and structured interviews with females who assuredly have working experience in the corporate finance department of firms listed in the Tehran Stock Exchange. Findings: It is concluded that the primary issue affecting the career vision of women is to achieve a better working environment. This issue admittedly can be considered as a reason for women to change their employer. The salaries and benefits are also the least important to them. Most women prefer to work in the educational part because of flexible working hours, and they broadly obtain almost no desire to work in the field of tax and cost accounting. Research limitations/implications: When answering the questionnaire or during the interviews, women are supposed to think about events that happened in the past, so it is recognized that they may selectively remember such events and interpret them with reference to the intervening events and the values that they hold at the time of the data collection. Moreover, all selected respondents may be naturally influenced by a desire to provide socially acceptable answers. Accordingly, the inherent limitations of the results are acknowledged. However, the prime focus of this paper is to consider and give voice to the female experience, which may or may not replicate the experience of their male counterparts. Practical implications: This paper contributes meaningfully to the debate on the issues affecting the career vision of women and may result in their departure. Originality/value: The impact of the dual work–life burden of women on career progression is assessed which contributes to the extant literature on the career progression of women in the context of developing countries such as Iran.